Procedure and Ethics of Triage: Rationing Healthcare During Pandemics and Disasters - Nurunnabi, Abu Sadat Mohammad; Banik, Bidhan Chandra; Adhikary, Sanchita; Kaiser, Amir Mohammad; Mohammad, Taneem; Hasan, Lt Col Mohammad Mahbubul; Das, Bilash Ranjan; Sutradhar, Probir Kumar (Mugda Medical College Journal, 2025)
The demand for healthcare services is likely to often exceed supply during pandemics and disasters, as we have experienced during the COVID-19 pandemic recently across the globe; Bangladesh is not an exception. In hospital settings with such constraining conditions especially in low-income countries like Bangladesh, institutions and individual providers of healthcare must use some moral framework for distributing the available resources efficiently and equitably during critical times. Triage is a military term in origin, being used to describe the prioritization of wounded soldiers and the use of available medical resources for maximal efficiency. Commonly recognized examples of triage include prehospital, catastrophic, emergency department, intensive care, waiting list (e.g., for lifesaving treatments such as surgical operation, dialysis, and organ transplants), and in battlefield casualties. Triage has the ability to substantially decrease mortality and morbidity by providing timely and specific care for critically ill patients on a priority basis. This paper aims to discuss triage procedure and ethical debates behind practice of triage during the pandemics and disasters. Mugda Med Coll J. 2025; 8(1): 60-65